Pembuatan Ready To Wear Look Gothic Dengan Variasi Detail Kulit Sintetis Dan Lukis Kain Motif Etnik Dayak - Arina Haq; Erni Septia Nur Fitri (Garina, 2023)
Gothic is a clothing style that is characterized by striking, mysterious, exotic, and complex dark features, in this study the author adds fabric painting with Dayak ethnic motifs on synthetic leather in a gothic look. This study aims to determine the process of making a ready-to-wear gothic look with variations of synthetic leather details and painting of Dayak ethnic motifs. The method used in this research process is a qualitative method. The process of making ready-to- wear which consists of a blazer, crop top, obi belt, and skirt begins with determining the fashion design, making patterns from basic patterns to breaking patterns, cutting materials, marking stitches, then sewing the sides of the crop top, combining with lining, attaching zipper and collar, sewing the sides and lining of the blazer, combining the main material and the lining, attaching the painting to the back, attaching the buttons, then sewing the sides and lining of the skirt, then combining the main material and the lining, reassembling, then combining the main material and the lining , reassembling, painting variations, installing tires on the waist, followed by combining all sides with a furing obi belt, sewing the waist, then installing chicken eyes, finally painting the Dayak ethnic motif on the skin, starting with making a pattern sketch of the motif, then installing it on the cloth, block the motif with white, and the last one gives color to the motif.